Loading Patterns of Rubber-Based Resistance Bands across Distributors - Alex D. Fuentes; Connor J. Smith; Todd C. Shoepe (MDPI AG, 2019)
Variable resistance implemented through concurrent use of rubber-based resistance bands and free weights is commonly used in training athletes. The purpose of this study was to examine the consistency of rubber-based resistance (RBR) band loading patterns across four distributors. Bands (n = 141) were obtained from online distributors (Rogue Fitness, EliteFTS, RubberBanditz, and Power Systems) across a spectrum of available widths (0.635, 1.270, 2.860, 4.450, 6.350, and 10.160 cm). At least five bands for each width were stretched in 5 cm increments from resting (100 cm) to twice resting length (200 cm) while tensile resistance was measured using a load cell integrated with a digital controller. Each band was tested twice on non-consecutive days producing an intertrial intraclass correlational coefficient (ICC) between 0.93–0.99 with a grand mean ICC across all repeated measures of 0.99. Statistical differences were observed in mean resistance for bands of equal thickness across distributors. Significant correlations were found between a range of tensile load expressed as a total load and band thickness (r = 0.658) and when expressed as a percentage (r = −0.386). This study is useful for strength and conditioning professionals and clinicians who should be cognizant of loading variability within both bandwidths and between distributors.